Efficient Production Planning Optimization: A Hybrid Grid Partitioning and Rough Set Approach for Fuzzy Rule Generation in Manufacturing Systems - Tao Song-slim Shi; Vieral wu Zhang (International Journal of Enterprise Modelling, 2021)
Efficient production planning is crucial for optimizing resource allocation and improving productivity in manufacturing systems. This research proposes a hybrid grid partitioning and rough set approach for fuzzy rule generation to address the challenges of production planning optimization. The integration of grid partitioning, rough set theory, and fuzzy logic enables a comprehensive analysis of input variables, handling uncertainty, and generating fuzzy rules for decision-making. The grid partitioning technique divides the input space into discrete cells, simplifying the optimization process. Rough set analysis within each cell identifies relevant features and dependencies, enhancing the understanding of the production system's behavior. The generated fuzzy rules capture linguistic relationships between input and output variables, facilitating context-aware decision-making. The evaluation and optimization of the rule set ensure the quality and effectiveness of the decision-making process. The proposed approach offers practical benefits, such as improved resource utilization, cost reduction, and enhanced productivity in manufacturing systems. However, the research acknowledges limitations in terms of the simplified scenario, data availability, computational complexity, parameter sensitivity, and generalizability. Further research is needed to validate and refine the framework in diverse industrial settings. The findings contribute to the advancement of production planning optimization and provide valuable insights for researchers and industry practitioners.